Urban Renewal Mechanism in Minority Nationality Areas of China in the New Era - Shen, Cheng; Zhang, Xuchen (AESOP, 2019)
With the development of society and economy in China, old cities need to transform to adapt to the modernization so that urban renewal is carried out in many cities. But China has something special that many urban areas are inhabited by minority nationalities. How to define the public interest in the process of urban renewal is complicated, the institutional problems are difficult and general theories and practices of urban renewal cannot be applied in such areas so there are few good practice in China now. A complete mechanism for this is essential. This article studies on renewal mechanism in the aspect of protecting public interests in minority nationalities areas. Firstly, a social research on different interest groups of minority areas in Changji is carried out to figure out what they are concerned about in urban renewal process; then a study on current cases of urban renewal in the existing minority areas is done to probe into the results and problems and combine with some theoretical analysis a complete summary can be made ; finally according to all the results mentioned above specific mechanism , implementation strategies and policies for the urban renewal process in these areas can be summarized.
Keywords: Minority Nationality Areas; Urban Renewal; Regional Transition; Mechanism